Perbedaan Tingkat Academic Burnout pada Siswa Ditinjau dari Jenis Sekolah SMA/SMK/MA - Putri, Aisyah Amini; Magistarina, Elrisfa (Lembaga Yasin AlSys, 2024)
The condition of exhaustion experienced by students as a result of excessive pressure to meet academic demands at school is also known as academic burnout. Burnout in students can lead to an increased risk of depression and decreased academic performance. The different operational curriculum used by each type of school results in students experiencing different academic demands. This study aims to see differences in the level of academic burnout among students in terms of the type of school, SMA / SMK / MA. The research method used is quantitative with a comparative causal approach. The subjects of this study were high school students in West Sumatra. The total subjects in this study were 165 people. The level of students' academic burnout was measured using the academic burnout scale adapted from Maharani (2019). The scale was adapted from a measurement tool developed by Schaufeli et al. (2002), MBI-SS (Maslach Burnout Inventory-Student Survey). The results showed that there was no significant difference in the level of academic burnout among students in terms of school type. However, the average score of MA students is higher than that of SMA and SMK students.